Social inequalities in health- do they diminish with age? Revisiting the question in Sweden 1999 - Beckman Anders; Lynch John; Gerdtham Ulf-G; Merlo Juan; Norlund Anders; Lithman Thor (BMC, 2003)
Abstract Background Individuals with low income have poorer health and should, therefore, have higher health expenditure than people with high income particularly in countries with a universal health care system. However, it has been discussed if social inequities in health diminish with age and we, hence, aimed to analyse this question. Methods We performed an age stratified cross-sectional analysis using averages, logistic and linear regression modelling of health care contacts, health care expenditures and mortality in relation to individual income in five groups by quintiles. The population consisted of all the 249,855 men aged 40 to 80 years living in the county of Skåne, Sweden during 1999. Results For working-age people (40-59 year old) we find a clear socioeconomic gradient with increasing probability of health care contact, relative expenditure and mortality as income decreased. The point estimations for 1st (highest)-2nd-3rd-4th and 5th (lowest) income groups were: (1.00-1.13-1.21-1.42 and 1.15), (1.00-1.16-1.29-1.69 and 1.89) and (1.00-1.35-1.44-2.82 and 4.12) for health care contact, relative expenditure and mortality respectively. However, in the elderly (75-80 year old) these point estimates were (1.00-0.83-0.59-0.61 and 0.39), (1.00-1.04-1.05-1.02 and 0.96) and (1.00-1.06-1.30-1.33 and 1.49). Conclusions As expected among working-age individuals, lower income was associated with higher health care contact, relative expenditure and mortality. However, the existence of opposite socioeconomic gradients in health care utilisation and mortality in the elderly suggests that factors related to a high income might condition allocation of resources, or that current medical care is ineffective to treat determinants of income differences in mortality occurring earlier in the lifecourse.